(untitled) (Vietnam Journal of Community Medicine, 2024)
Overview: Circumcision is a simple surgery, performed not only in hospitals but also in private clinics. There are many general practitioners and surgeons learn and practise this method due to this simple kind of surgery. This leads to more and more severe complications stemmed from “circumcision”. There are some negative repercussions such as bad scars, buried penis, and penile curvature. Objective: This article aims to report a case of penile curvature complication after circumcision and penile lengthening surgery, and to share experiences in diagnosis and treatment. Case report: A 26-year-old male patient presented with penile curvature after circumcision and penile lengthening surgery. Diagnosis is mainly based on clinical symptoms. Surgery to correct curvature and repair scars with multi-Z plasty. Discussion: Discussing clinical characteristics and difficulties in devising surgical strategies. The rarity of complications of penile curvature after circumcision surgery is highlighted. Conclusion: If circumcision is not performed properly and safely, its complications will be obviously risky, and the treatment of this late complication is currently challenging.